Diagnosis of Primary Hyperventilation Syndrome by Polysomnography: A Report of Two Cases - Tarang N Sheth; Steven Kesten (Canadian Respiratory Journal)
Two cases of primary hyperventilation syndrome misdiagnosed as asthma are reported. Polysomnography was used to diagnose the syndrome and to confirm the psychogenic etiology of the patients' symptoms.